A pediatric case of cellulitis caused by Stenotrophomonas maltophilia with subcutaneous microvascular thrombosis and diffuse hemorrhage. Issue 6 (24th July 2021) - Inoue, Emi; Arase, Noriko; Miyamura, Takako; Wataya, Tomohiro; Tanaka, Yusuke; Kashiwagi, Nobuo; Sakai, Hiroshi; Nojima, Satoshi; Fujimoto, Manabu
Abstract : A pediatric case of cellulitis caused by Stenotrophomonas maltophilia after bone marrow transplantation was experienced. Pathologically, multiple microvascular thrombi and diffuse hemorrhage due to S .  maltophilia cellulitis were observed in the subcutaneous tissue. This is the first report of pathological findings of such microvascular thrombi coexisting with hemorrhage in maltophilia infection.